Zikir tarekat Qodiriyah Naqsyabandiyah dalam pemulihan dadah: kajian keberkesanan di pondok remaja Inabah (1) Malaysia - Abu Bakar, Ahmad Mansor (2019)
Youth is an asset of a country, and they are the generation to inherit the country in the future. However, they have faced a number of challenges, including those who are involved in drug abuse. In Malaysia, the rate of drug abuse among youth is increasing from year to year. This scenario makes the country seriously look at this condition. There are several drug rehabilitation centers using the zikir approach as a means of healing. One of the drug rehabilitation center is the Inabah 1 Malaysia Youth Camp, which uses the Naqsyabandiyah Qadiriyah zikir as an alternative treatment to rehabilitate the drug addicts. The objectives of this study are to examine the concept of Naqsyabandiyah Qodiriyah Zikir, to detail-up the Naqsyabandiyah Qodiriya Zikir, and to analyze the effects of this zikir on the rehabilitating drug addicts among youth. This study uses qualitative research methods involving library research, interviews and observation. Library research is aimed at obtaining data related to the concept and method of zikir. The interviews with two counselors and seven trainees at Inabah (1) Malaysia Youth Camp were conducted to analyze the effects of zikir. The data were analyzed using inductive and deductive methods. The findings show that the Naqsyabandiyah Qodiriyah zikir was able in restoring the spirit and rehabilitating the drug addicts and moreover to provide positive effects to the trainees. These effects were felt by the existence of positive changes in physical, behavioural, and feelings. These changes can be seen and felt by the trainees after undergoing a remedial treatment for at least 40 days. The numerous amounts of zikir within a long period of time produce positive impacts on the trainees. This zikir treatment method could also be extended as a spiritual-based rehabilitation treatment module in other places.